A snow day for Amos McGee - Stead, Philip Christian (Roaring Brook Press, 2025)
Zookeeper Amos McGee passes out warm knits to the animals in anticipation for snow that never arrives, but when a surprise snowfall blankets the zoo, the zookeeper and his animal friends enjoy the snowy day together.